(untitled) (Vietnam Journal of Community Medicine, 2024)
Schizophrenia is a severe, progressive psychotic disorder with diverse clinical manifestations. In the treatment procedure, besides taking medicine regularly, diet and nutrition also play an important role. The problems related to eating behaviors among schizophrenia patients can be caused by positive symptoms (delusions of being poisoned, hallucinations...) or negative symptoms (dullness, lack of purposes). Each schizophrenia patient may have different eating/nutrition problems. Therefore, it is extremely necessary to pay attention to the eating behaviors of schizophrenia patients in both the acute and maintenance treatment phases. Objective: The study aims to describe the characteristics of eating behavior among schizophrenia patients receiving daycare treatment at Mai Huong Daycare Psychiatric Hospital, 2022. Subjects and research methods: A descriptive study on 108 schizophrenia patients receiving daycare treatment at Mai Huong Daycare Hospital from February 2022 to October 2022. Results: Eating behaviors such as anorexia, changes in appetite, and less drinking were common symptoms in the study group, with the same results in both men and women. The prevalence of anorexia symptoms in the study group is 51.9%. The sex difference in anorexia group is statistically significant with p-value = 0.04. The rate of changes in taste in the study group was 66.7%. Symptoms of resistance to eating were found in 5 acute-symptom cases. This difference was statistically significant with 99% confidence (p = 0.00). In the study, there were no binge eating patients as well as dirty eating patients. The percentage of patients who rarely drinks in the study group was 63.9%.